2023
DOI: 10.1186/s12934-023-02031-3
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable bacterial cellulose production by Achromobacter using mango peel waste

Abstract: Bacterial Cellulose (BC) is still the most renewable available biopolymer produced in fine nature from alternative microbial sources as bacteria. In the present study, newly BC producing bacteria were successfully isolated from acidic fruits. The most potent producer was isolated from strawberry and identified genetically using 16 s rRNA technique as Achromobacter S3. Different fruit peels were screened to produce BC using the cheapest culture medium. Among them, Mango peel waste (MPW) hydrolysate proved to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…According to the results, it was highlighted that the carbon and nitrogen sources of these waste were found to be sufficient for microbial growth. In a more recent study conducted by Hasanin et al (2023), mango peel waste hydrolysate was found to be a significant inducible fermentation medium with no need for extra nutrients and increasing the BC yield about 2.5 fold in comparison to the HS medium. So, it can be re-emphasized that the composition of the fermentation medium is a critical determinant factor in both the production yield and cost.…”
Section: Production Mediummentioning
confidence: 93%
“…According to the results, it was highlighted that the carbon and nitrogen sources of these waste were found to be sufficient for microbial growth. In a more recent study conducted by Hasanin et al (2023), mango peel waste hydrolysate was found to be a significant inducible fermentation medium with no need for extra nutrients and increasing the BC yield about 2.5 fold in comparison to the HS medium. So, it can be re-emphasized that the composition of the fermentation medium is a critical determinant factor in both the production yield and cost.…”
Section: Production Mediummentioning
confidence: 93%
“…The gut microbiota in the dietary transition groups were associated with more beneficial nutrient metabolism and transport than observed in the AD group. For example, increased abundance of Achromobacter helps the host degrade cellulose [43,44], and increased abundance of Rhodococcus contributes to the metabolism of sugars and aromatic compounds [45,46]. These changes in the gut microbiota synergistically promoted protein synthesis, thus resulting in significantly greater silk production efficiency in the dietary transition groups than the AD group.…”
Section: Dietary Transition Increases Resistance and Silk Production ...mentioning
confidence: 99%
“…Thus, according to the sequencing data of the complete metagenome community, the microbiome of the Medusomyces gisevii is represented, in fact, by bacteria of three genera. Representatives of the genera Achromobacter [31] and Komagataeibacter are known to produce bacterial cellulose [32].…”
Section: Microbiome Characterization Of Symbiotic Culture Medusomyces...mentioning
confidence: 99%